Several Antecedent Variables That Influence Entrepreneurial Intention - Endang Sulistiyani; Azizah Azizah; Winarto Winarto; Isnaini Nurkhayati; Febrina Indrasari (Cita konsultindo, 2024)
The purpose of this study was to analyze several antecedent variables, namely adversity quotient, family support and digital literacy in influencing entrepreneurial intention. The object of research is students majoring in Business Administration at Politeknik Negeri Semarang. The sample was taken using purposive sampling method. Respondents are students who have received entrepreneurship courses and conduct business activities. Data were collected using questionnaires, and processed using Structural Equation Modeling analysis. Based on the results of the analysis, the three hypotheses that have been proposed show two hypotheses proved to have a significant positive effect and one hypothesis is the relationship of family support has no effect on entrepreneurial intention. The dominant influence between variables is shown from the relationship between adversity quotient to entrepreneurial intention.